Step-by-step explanation:
Let us assume that the cost of per pound of apples = $ x
Assume that the cost of per pound of potatoes = $ y
Now, according to question:
The cost of 8 pounds of apples and 5 pounds of potatoes = $25.50
⇒ Cost of 8 pounds of Apple + Cost of 5 pounds of potatoes = $25.50
⇒ 8 x (Cost of 1 pound apple) + 5 x ( cost of 1 pound potato ) = $25.50
⇒ 8 x + 5 y = $25.50 .... (1)
⇒ 5 y = 25.5 - 8 x
Similarly,
The cost of 3 pounds of apples and 10 pounds of potatoes = $18.50
⇒ 3 x + 10 y = $18.50 .... (2)
or, 1.5 x +5 y = $ 9.25 ( dividing the equation by 2)
⇒ 5 y = 9.25 - 1.5 x
Now, comparing both equations,we get:
25.5 - 8 x = 9.25 - 1.5 x
⇒ 25.5 - 9.25 = 8 x - 1.5 x
⇒ 16.25 = 6.5 x
⇒ x = 2.5
Putting this value of x in 5 y = 9.25 - 1.5 x, we get:
5 y = 9.25 - 1.5 (2.5)
⇒ 5 y = 5.5
⇒ y = 1.1
So, the cost of 1 pound of apples = $2.5
The cost pf 1 pound of potatoes = $1.1
The ordered pair (x,y) is given as : (x,y) = (2.5,1.1)